The language of appraisal in British advertisements - Križan, Agata (ELOPE (Ljubljana), 2016)
The article explores the occurrence and frequency of use of attitudinal judgement in British advertisement texts. Judgement, as one of the main attitudinal categories in the discourse-semantic appraisal model (Martin and White 2005), is concerned with the evaluation of human character and behaviour. The article focuses on the judgement categories of capability and propriety, as the research described concludes that they are the most frequently occurring of the judgement categories. Some typical instances encoding capability and propriety are discussed in terms of explicit and implicit manifestation. The article demonstrates that capability and propriety often participate in attitudinal double-coding due to the brevity of advertising texts and the creativity of advertising language. Capability and propriety are strongly socially motivated: they impose values upon the potential consumer, and hence upon society, and through them create social roles for the participants in the advertising interaction.
Keywords: dvojno kodiranje odnosov; medosebni pomen; presoja; reklamni oglasi; sposobnost; ustreznost moralnim načelom; vrednotenje